CYCLICITY & CHAOTICS IN POST-CRISIS CONTEXT - BURCIU, Aurel; KICSI, Rozalia (Annales Universitatis Apulensis Series Oeconomica, 2014)
The current global crisis has generated in economic and management theory numerous questions/ dilemmas, because the magnitude of the crisis surprising the entire capitalist world. Juglar cycles, Kuznets cycles and Kondratieff cycles are well known in economic theory but their findings have been deliberately ignored by policy makers. The current theory discusses about the chaotics of the business environment, the instability and highly sinuous evolution of economic life. Regarding the study of cyclicity in business at the firm level, this subject has been and remains more complex by its very nature. From the perspective of our research, we aim to highlight the relation of interdependence between the macroeconomic cycles and business development at the company/firm level.